Connected multisensory room with data analytics for cognitive impairment therapy/ Muhammad Akmal Jamil - Jamil, Muhammad Akmal (2018)
Multisensory room (MSR) is a prescription of therapy sessions for stimulating senses involving patient and therapist interaction. Therapy sessions are known to take effect at different rate depending on patient’s condition and response, often across a long period of time for it to be noticeable. Based on this reason, there is a need to improve data collection and analysis that will allow clinical data analytic. This project presented a multisensory room design that offers added connectivity for data storage and configuration for data analytics. The main objective is to develop effective data collection through multisensory therapy session. Second objective is to demonstrate data analytics using predictive model towards data collected from the multisensory room. Under this framework, the therapy would be divided to five sub-modules. First, when the patient meets the doctor or therapist assessment, to be given the clinical prescription. Second is therapist assessment, followed by the MSR session, then the post-MSR therapist assessment. The treatment is concluded by data analytics. MSR performed analysis to assist doctor’s review of the prescribed MSR using artificial data that is incorporated into behavioural checklist and patient data. Results show that in a connected environment of a multisensory room, data analytics involving visual representation and linear regression predictive model using SAS Viya is able to produce patient response analysis. The analysis will be useful to support doctor’s assessment of the patients that have undergone therapy sessions.